Dinâmica de população de Tapirira guianensis AUBL. (Anacardiaceae), em áreas de restinga e cerradão do Estado de São Paulo - Baldoni, Raquel Negrão (Universidade Federal de São Carlos, 2010)
The situation of a population can only be assessed through demographic studies, considering its dynamics in terms of changes on fecundity, recruitment and mortality of individuals. Considering the peculiarities of the vegetation in State of Sao Paulo and the ability that some plant species have to occupy some of these different ecosystems, this study aims to assess the ecology of two populations of Tapirira guianensis Aubl. (Anacardiaceae), in the restinga located at the Parque Estadual da Ilha do Cardoso and in the cerrado at the Estação Ecológica de Assis. This project was carried out within the permanent plots of the project funded by Biota. There, were randomly allocated 50 plots of 20m x 20m (total area of 2 ha/environment) and all individuals of Tapirira guianensis found within these plots were identified and measured. Individuals were classified into ontogenetic stages in accordance with the Troll´s Model. We found allometric differences between the populations that might be related to the phenotypic plasticity to environmental variations. The population structure of T. guianensis was significantly different between restinga and cerrado (t-test, p <0.001). In the restinga, the structure shows the form of "j" reverse while in the cerrado, the population does not present this form of distribution. The difference between the populations is mainly due to the absence of seedlings in the cerrado. We found no differences between plant density and soil types, which suggest that T. guianensis is indifferent to soil caracteristics. The population growth rate indicated that both populations from restinga (λ = 0.96) and from cerrado (λ = 0.91) are close to 1.0, so these two populations seems to be in equilíbrium. However, we verified differences on demographic parameters between these populations. We suggest that variation between populations is related to phytogeographic conditions in restinga and cerrado, and to the interaction between various environmental factors.
Keywords: Ecologia da população; Estrutura da população; Dinâmica da população; Plasticidade fenotípica; Floresta de restinga; Cerrado; Architectural model; Structure population; Dynamic population; Tapirira guianensis; Restinga; Cerradão; CIENCIAS BIOLOGICAS::ECOLOGIA